Wellbore stability research based on transversely isotropic strength criteria in shale formation - Xiangsen Gao; Min Wang; Xian Shi; Peng Dai; Mingming Zhang (Soils and Foundations)
Borehole instability is a significant concern when drilling inclined wells through bedding layers. Traditional drilling techniques have encountered various challenges due to shale’s tendency to shear and slide along faults, joints, and weak planes. This study explores the mechanisms behind borehole instability in layered shale formations by conducting triaxial compression experiments on shale samples with varying bedding angles. It examines the anisotropic nature of shale properties and how strength varies with bedding angle. By integrating anisotropic strength criteria and transversely isotropic stress models around wells, the study develops a predictive model for borehole instability in layered shale formations and assesses the impact of different anisotropic strength criteria on predicting collapse pressures. The results show that shale’s elastic modulus and Poisson’s ratio have an inverse relationship with the increasing bedding angle. Besides, the patchy plane of weakness model, characterized by the parameter η, accurately predicts strength during inherent shear failure, sliding along bedding planes, and mixed failure. In contrast, the single plane of weakness model yields the highest collapse pressure predictions, while the Mohr-Coulomb criterion provides the lowest. The patchy plane of weakness model offers intermediate and more realistic pressure predictions. Moreover, while the type of in-situ stress does not affect the magnitude of collapse pressure, it influences the distribution characteristics of the collapse pressure cloud map. These findings, which account for shale anisotropy in minimum mud pressure analysis, have the potential to enhance drilling efficiency in practical applications.